Food fortification with iron and vitamin A - Zancul, Mariana Senzi (Medicina (Ribeirao Preto), 2004)
Micronutrients deficiencies such as vitamin A and iron and iodine, are the greatest nutrition and public health problems all over the world in developing countries, including Brazil. This deficiency affects infants, preschool children, teenagers, pregnant and women in fertile age. Food fortification, addition of vitamins and minerals to food of massive use, to guarantee desirable intake of these nutrients is an efficient way to prevent micronutrient deficiency, such as iron and vitamin A. Food fortification is a relatively simple process, but it requires the best choice of the food to be used as vehicle as well as the appropriated selection of the compound to be added. There are several vitamins and minerals used in food fortification. The use of industrial fortification of foods has been one of the best choices to control micronutrients deficiency all over the world. In this work aspects of food fortification with iron and vitamin A are reported and discussed. These deficiencies affect the largest number of persons in the developing world, including Brazil.